Formulation, stability and analytical method validation of chasteberry (Vitex agnus-castus L.) extract in solid oral dosage forms - (:unkn) unknown (MARMARA UNIV, 2019)
Premenstrual syndrome (PMS) is a common condition that affects 90% of menstruating women on emotions, behaviours and physical health. Vitex agnus-castus L. also known as chasteberry or chaste tree is long being used for its health benefits on feminine problems like PMS and hyperprolactinemia. There are also some prescription medicines to ease the symptoms of PMS. While dietary supplements containing medicinal plants could be found everywhere with the lack of quality and standardisation, there are only a few registered traditional herbal medicinal products available on the market containing agnus-castus fruit extract. In this study we developed a stable film coated oral formulation and fully validated the analytical methods to quantify the extract in dosage forms to fulfil the requirements of CTD module 3 while registering the traditional herbal medicinal product according to European Union legislations.
Keywords: Chasteberry; Vitex agnus-castus; validation; formulation; stability